Cementless reverse total shoulder arthroplasty in a patient affected by Osteogenesis Imperfecta: a case report and review of the literature. - Mancuso, Francesco; Di Benedetto, Paolo; Marchetti, Andrea; Ghassempour, Dario; Beltrame, Alessandro; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work: Osteogenesis Imperfecta is a rare genetic condition. The use of total shoulder arthroplasty in these patients is very uncommon, with only two cases reported in the literature. This study describes a cementless reverse total shoulder arthroplasty (rTSA) for a multi-fragmented fracture in a patient affected by Osteogenesis Imperfecta (OI) type 1 and aims to review literature results of shoulder replacement in patients affected by this uncommon condition. Methods: the case of a woman affected by OI type 1 treated with a cementless rTSA for a multi-fragmented proximal humerus facture is reported. Focusing on the fixation technique, a research of all articles regarding the orthopaedic treatments in patients affected by Osteogenesis Imperfecta was performed and compared to the techniques used in the unaffected population. Result: Our patient shows good results in terms of clinical and radiological outcomes at the short term follow up. Few studies treat the orthopaedic manifestation of this rare genetic condition and only two are focused on shoulder arthroplasty. Cement is the preferred method for fixation in both papers. Conclusion: Cementless reverse shoulder arthroplasty may be an option in patients affected by OI type 1, although literature seems to support cement as the fixation method of choice.